Measuring Tourism Social Carrying Capacity: An Exploratory Study of Social Dynamics in Ecotourism Development of Cirebon - RUSLI, Meizar; AVENZORA, Ricky; SUNARMINTO, Tutut; MALIHAH, Elly (Journal of Environmental Management and Tourism, 2024)
The carrying capacity of tourism activities is a crucial thing that needs attention, considering that it is closely related to sustainable development to maximize the future of human rights to resources. The study and concept of tourism carrying capacity can be assessed through a comprehensive research methodology based on existing social interaction analysis space. Areas of tourist and non-tourist attractions in the activity centre of Cirebon City are the empirical application of this study. Some of the findings from the analysis show that negative social interactions exist in spaces that are directly or indirectly affected. Therefore, the procedures and results of this study can be of particular concern to managers, planners, developers and marketers in the tourism sector.